Integrated management of rajmash diseases in dry temperate region of north-western Himalayas - AMAR SINGH, D.K. BANYAL* and (Indian Phytopathology, 2007)
Common bean (Phaseo/us vulgaris L), is the only pulse crop grown in dry temperate zone (Lahaul valley) of Himachal Pradesh. It suffers from two fungal diseases; web blight (Rhizoctonia so/ani) and white rot (Sc/erotinia sc/erotiorum). Web blight severity ranged from 7.5 - 27.5 per cent and that of white rot ranged between 14.3 - 30.0 percent during 1998 to 2002 in Lahaul valley. To manage these diseases, experiments were conducted from 1998-2003 using fungicides and bioagents. Seed treatment with carbendazim alone and in combination with its spray provided maximum disease control of both web blight and white rot diseases. Soil application of Trichoderma viride managed both the diseases better as compared to seed treatment. Integration of seed treatment with carbendazim (2.5 g/kg seed), its single foliar spray (0.05 per cent) at the time of flowering and soil application of T. viride (2.5kg/62kg FYMlha) managed the diseases upto 83.5 per cent (web blight) and 70.8 per cent (white rot) along with increase (68.8 per cent) in the crop yield.